2019
DOI: 10.4028/www.scientific.net/msf.962.194
|View full text |Cite
|
Sign up to set email alerts
|

On the Development of a Space Satellite Mirror with Intrinsic Self-Healing Properties

Abstract: In the aerospace industry the demand for very strong and light components is a permanent objective and for this matter composite materials began to be used at large scales in construction of space structures. The presence of micrometeoroids and orbital debris in space, particularly in the lower earth orbit, presents a continuous hazard to orbiting satellites, spacecraft, and the International Space Station. Among the 8700 objects larger than 10 cm in Earth Orbits, only about 6% are operational satellites and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Since Kessler et al 51 first reported self-healing of carbon fibers reinforced polymer (CFRP) composites with microcapsules in 2003, few studies have reported FRP composites with self-healing capabilities being used in aerospace, weaponry and other critical applications in the last two decades. 52 One of the key factors limiting the application of self-healing composites is that certain contradictions still exist between the self-healing properties of composites and their mechanical as well as thermal properties. How to maintain or even improve the original properties of composite materials meanwhile making them self-healing is the goal that researchers are currently pursuing.…”
Section: Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Kessler et al 51 first reported self-healing of carbon fibers reinforced polymer (CFRP) composites with microcapsules in 2003, few studies have reported FRP composites with self-healing capabilities being used in aerospace, weaponry and other critical applications in the last two decades. 52 One of the key factors limiting the application of self-healing composites is that certain contradictions still exist between the self-healing properties of composites and their mechanical as well as thermal properties. How to maintain or even improve the original properties of composite materials meanwhile making them self-healing is the goal that researchers are currently pursuing.…”
Section: Overviewmentioning
confidence: 99%
“…Currently, the research on self‐healing FRP composites is still in the laboratory stage. Since Kessler et al 51 first reported self‐healing of carbon fibers reinforced polymer (CFRP) composites with microcapsules in 2003, few studies have reported FRP composites with self‐healing capabilities being used in aerospace, weaponry and other critical applications in the last two decades 52 . One of the key factors limiting the application of self‐healing composites is that certain contradictions still exist between the self‐healing properties of composites and their mechanical as well as thermal properties.…”
Section: Overviewmentioning
confidence: 99%